Strength training anatomy - Delavier, Frederic (Human Kinetics, 2010)
With new exercises, additional stretches, and more of Frédéric Delavier's signature illustrations, you'll gain a whole new understanding of how muscles perform during strength exercises. This one-of-a-kind best-seller combines the visual detail of top anatomy texts with the best of strength training advice. Many books explain what muscles are used during exercise, but no other resource brings the anatomy to life like Strength Training Anatomy. Over 600 full-color illustrations reveal the primary muscles worked along with all the relevant surrounding structures, including bones, ligaments, tendons, and connective tissue. Like having an X-ray for each exercise, the anatomical depictions show both superficial and deep layers and detail how various setup positions affect muscle recruitment and emphasize underlying structures. New pages show common strength training injuries in a fascinating light and offer precautions to help you exercise safely. Author and illustrator Frédéric Delavier is the former editor in chief of the French publication PowerMag. He is a journalist for Le Monde du Muscle and a contributor to Men's Health Germany and several other strength training publications